The layered games framework for specifications and analysis of security protocols. (6th November 2008) - Herzberg, Amir; Yoffe, Igal
We establish rigorous foundations to the use of modular and layered design for building complex distributed systems, resilient to failures and attacks. Layering is a key to the design of the internet and other distributed systems. Hence, solid, theoretical foundations are essential, especially when considering adversarial settings. A protocol realises a layer (over some lower layer) if it 'wins' with high probability, a specified game, when running over any implementation of the lower layer. This is in contrast to existing frameworks allowing modular design of cryptographic protocols, where protocols must emulate an ideal functionality. Ideal functionalities are a very elegant method for specifications, but we argue that often, game-based specifications are more appropriate, to avoid over-specification ('forcing' a particular design) and under specification (e.g. protocols that work poorly for realistic adversaries). Our results allow specification and analysis of each layer independently, then combining the results to ensure properties of the complete system.